Examining the Integration of Islamic Values within English Classrooms at SMPIT in West Lombok through the Lens of Teaching Tools - Imansyah, Imansyah; Utama, I Made Permadi (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
The establishment of Integrated Islamic Schools addresses perceived gaps in the National Education System, particularly in addressing modern scientific and technological challenges. Concerns about declining moral values among students, including issues like substance abuse and juvenile delinquency, have driven this response. This study examines how integrated Islamic schools in West Lombok, NTB, incorporate Islamic values into English language education. Using a descriptive qualitative method, the research focused on teaching tools such as syllabi and lesson plans, analyzing how Islamic values were integrated. The subjects included three English teachers and two vice principals from different schools. The analysis revealed that Islamic values were not incorporated into the syllabi, lesson plans, or teaching procedures, as required by JSIT (Integrated Islamic School Network). Interviews indicated that teachers neglected curriculum analysis and failed to define the Islamic values to be included, largely due to insufficient training. Consequently, the anticipated integration of Islamic values in English language learning has not been achieved. A review of lesson plans and syllabi confirmed this gap, highlighting a significant shortfall in the expected implementation of Islamic value integration in these schools.